CEDERA OTAK TRAUMATIS - Asrizal Asril; Sari Nikmawati (Nusantara Hasana Journal, 2026)
Traumatic brain injury (TBI) is a major cause of morbidity and mortality worldwide, particularly among the productive-age population. TBI occurs as a result of external mechanical forces that lead to structural and functional disturbances of the brain. The impact of traumatic brain injury is not limited to the acute phase but may also result in long-term neurological impairment. This article aims to discuss traumatic brain injury based on journal reading of the literature used in the source paper, including its definition, mechanisms of injury, pathophysiology, and diagnostic approaches. The writing method employed is a literature-based journal reading. The results of the review indicate that primary and secondary injuries play an important role in determining clinical outcomes, and that neuroimaging examinations are essential in the diagnosis and evaluation of traumatic brain injury.